A Dynamic Systems Approach to the Representation of Policy Implementation Processes in a Multi-Actor World - Kovalevsky, Dmitry V.; Hewitt, Richard; Boer, Cheryl de; Hasselmann, Klaus (Discontinuity, Nonlinearity, and Complexity, 2026)
Implementation of any policy involves negotiation between multiple actors, and is therefore susceptible to a dynamic systems modelling approach. In this paper, we make an attempt to develop a family of dynamic systems models of policy implementation in such a multi-actor world by translating an existing, semi-quantitative, application of two theoretical approaches, Contextual Interaction Theory (CIT) and Participatory Action Research (PAR), into a quantitative dynamic framework. We explore various alternative actor-based dynamic systems for this proposed Participatory Contextual Interaction Theory (PCIT), including linear, piecewise linear, and strongly nonlinear models. Analytical results are supplemented with results of numerical simulations. One of the goals of the modelling exercise is to advance the actor dynamics module in the APoLUS land use cellular automata model; illustrative examples of the incorporation of actor dynamics models developed in the present paper into the computation of APoLUS transition potentials are provided.